Investigation of Common Indications for Fetal Radiation Rules Bypass in X-Rays Practices among Healthcare Professionals in Rwanda - Fabrice, Niyigena; Emmanuel, Iradukunda; Philemon, Iradukunda; Adam Moyosore , Afodun; Mecthilde, Mukangendo; Mustapha Akajewole, Masud; Isabelle, Kayitesi; Emmanuel, Singaye; Mugisha, Gad; Khadijah Kofoworola, Quadri (Journal of BP Koirala Institute of Health Sciences, 2025)
Background: The use of X-ray imaging during pregnancy necessitates careful consideration to minimize fetal radiation exposure. Despite established safety protocols, instances of bypassing these guidelines raise concerns about potential risks to fetal health. This study aimed to explore the prevalence and underlying reasons for the bypass of fetal radiation safety rules in X-ray practices within Kigali City. Additionally, it sought to assess the awareness and training levels among healthcare professionals regarding these protocols. Methods: A quantitative cross-sectional approach was employed, utilizing convenience sampling to gather data from (n=53) healthcare professionals in Kigali City. The choice of convenience sampling was informed by the dispersed locations of the healthcare professionals. Information was collected through structured questionnaires, with subsequent analysis performed using Chi-square statistics with the aid of Statistical Package for Social Sciences (SPSS) version 21 to elucidate patterns and draw conclusions. Results: Our study revealed radiographers who were unfamiliar with the rules (and tailored-protocols) were more likely to ignore them (13 out of 18); compared to those who were familiar (8 out of 35). The relationship between familiarity with fetal radiation rules and bypass-behaviour among radiographers is statistically significant with (χ² = 11.24, df = 1, and p = 0.001). Conclusion: The study highlights a critical need for reinforced training and awareness among healthcare professionals regarding fetal radiation exposure guidelines. Enhanced educational efforts, coupled with stringent adherence to safety protocols, are imperative to safeguard fetal health during radiological examinations.